Essential oil composition of Zanthoxylum armatum leaves as a function of growing conditions. Issue 1 (1st January 2019) - Phuyal, Nirmala; Jha, Pramod Kumar; Raturi, Pankaj Prasad; Gurung, Sumitra; Rajbhandary, Sangeeta
ABSTRACT: Variation in the composition of leaf essential oils of Zanthoxylum armatum in relation to altitude and soil chemistry was analyzed in Nepal. The essential oil was extracted by Clevenger apparatus and the components were analyzed through GC-MS. The results showed that: Yield of the essential oil obtained from the hydro-distillation of dried leaves ranged from 0.16% to 0.50%. GC-MS analysis revealed total of 17 compounds in the essential oil from the dried leaves of Z. armatum from different altitudes and populations (wild and cultivated). The three major components, linalool, limonene and undecan-2-one, present in higher proportion in all the samples were analyzed. Other components tridecan-2-one, myrcene, cinnamate(E)-methyl and alpha-bergamotene were also identified in most of the samples but in lower proportions. The highest number of components (12) was identified from the wild samples collected from 1990 m and the lowest number (7) was from 1060 m (wild) and 2030 m (cultivated populations). Linalool, a major component was found in higher amount (64.88%) at the lowest altitude of 1060 m. Results of the present study showed that the altitude, soil chemistry, and growing conditions significantly affect the essential oil components in Zanthoxylum armatum.